Javanese Local Wisdom-Based Corporate Social Responsibility at PT PLN (Persero) UP3 Mojokerto - Singgih Bayu Indra Hermawan; Eka Ananta Sidharta; Endang Sri Andayani (International Journal of Economics, Business and Innovation Research, 2023)
The purpose of this study is to explain how the practice and disclosure of Corporate Social Responsibility are based on local culture and local wisdom. This study uses Stakeholder Theory and Enterprise Theory and the approach used in this study is qualitative research using a type of case study approach. A case study is an approach or strategy that "focuses on understanding the dynamics present within a single setting" by conducting in-depth interviews with informants. The implementation of Corporate Social Responsibility at PT PLN UP3 Mojokerto is an activity that aims to prioritize corporate ethics and culture in its social investment, and organizations can provide a return on benefits by showing good performance in terms of entities and governance by incorporating elements of culture and local wisdom in it. On the other hand, cultural diversity is rich and still holds traditional values based on local wisdom in carrying out organizational activities, especially in terms of social and environmental accounting. This thick Javanese local wisdom has become a tradition and a necessity in the application of social and environmental accounting, especially in the implementation and disclosure of Corporate Social Responsibility. This is used to maintain good relations between the organization and surrounding stakeholders. This study aims to complete the information gap regarding the practice and disclosure of Corporate Social Responsibility related to the local wisdom of a region.